The bases of economic geography : - Boyce, Ronald R. (Holt, Rinehart and Winston, 1974)
Part of a series on Economics Supply-demand-right-shift-demand.svg A supply and demand diagram, illustrating the effects of an increase in demand Index Outline Category HistoryBranchesClassification [show] ConceptsTheoryTechniques [show] By application[show] Notable economists[show] Lists[show] Glossary[show] Emblem-money.svg Business and economics portal vte Economic geography is the study of the location, distribution and spatial organization of economic activities across the world. It represents a traditional subfield of the discipline of geography. However, many economists have also approached the field in ways more typical of the discipline of economics.